Immunoexpression of ALDH1A1, FGFR2, CD44 and Caspase-3 in Oral Squamous Cell Carcinoma and Leukoplakia: A Pilot Study - Boza Oreamuno, Yadira V. (2023)
Current research highlighted the importance to recognize feasible biomarkers for early diagnoses and treatment in oral cancer. Our study analyzed the expression and spatial distribution of ALDH1A1, FGFR2, caspase-3, and CD44 in Oral Squamous Cell Carcinoma (OSCC) and leukoplakia with and without oral mucosal dysplasia. Paraffin-embedded samples of OSCC (n=5), leukoplakia with (n=5) and without (n=5) dysplasia obtained by incisional biopsies were processed using conventional histochemical techniques. Immunohistochemistry was performed using antibodies against ALDH1A1, FGFR2, caspase-3, and CD44. Images of the immunohistochemically stained tissue sections were analyzed according to the intensity of the immunostaining of each marker and classified in Scores. The Kruskal-Wallis test was performed (p≤0.05). Our results demonstrated a statically difference in the expression of all immunomarkers between OSCC and leukoplakia without dysplasia, being more significant in FGFR2 and ALDH1A1. Within the limitations of this study, our data showed that all biomarkers were overexpressed in OSCC and leukoplakia with oral mucosa dysplasia, suggesting that the presence of dysplasia is a significant clinic-pathologic predictor for malignant transformation.